Top gun - Cash, Jim; Epps, Jack; Cruise, Tom 1962-; McGillis, Kelly 1958-; Kilmer, Val 1959-; Edwards, Anthony 1962-; Skerritt, Tom; Faltermeyer, Harold
At the elite Navy Fighter Weapons School, cocky, young pilots compete against one another in the air as well as on the ground